Sujeto, tiempo e historia en la poesía de Magdalena Chocano - Ruiz Echegaray, Matías (2024)
This paper analyses Magdalena Chocano's book of poems Objetos de distracción (2016) in dialogue with her earlier books Poesía a ciencia incierta (1982) and Estratagema en claroscuro (1986). The aim is to identify and explore the different ways in which the notions of subject, time and history are represented in this work. It is argued that Chocano's poetry questions the conventions of representation of the poetic subject, time and history. It shows the transition from the construction of a paradoxical subject —visionary and vulnerable— to a decentralised voice without identity marks. It also investigates the configuration of a discontinuous temporality in the author's later poetry, which shares with her earlier works the rejection of a homogeneous and linear time. It is proposed that her poetry shows a fragmentary and discontinuous vision of history, against the current of epic or totalising discourses